Competition and Price Levels in the Retail Gasoline Market - Marvel, Howard P. (The Review of Economics and Statistics, 1978)
Retail gasoline prices in 22 cities were surveyed to identify the effects of competition on price during the 1964-1971 period, when gasoline supplies were relatively normal and price wars were common. The informational theory of oligarchy is used to derive regression results and determine their market relevance. The 1965 price restoration move led by Texaco effectively eliminated small marketers selling at supra-competitive levels. The findings support the conclusion that collusive pricing was practiced to some extent during the period until competitive pricing returned in 1970. 8 references.